MEMBONGKAR ESENSI DASAR SILA PERTAMA PANCASILA: INTERNALISASI PEMIKIRAN ISLAM MOHAMMAD ARKOUN DALAM KONSEP KETUHANAN YANG MAHA ESA - Annafikarno, Nadila Mahilaveda; Alfarizy, Ahmad (Journal of Islamic Law Studies, 2019)
Belief in the One and Only God as the first principle of Pancasila has hierarchical implications which are the prerequisites for realizing the next precepts. If traced, Soekarno had the concept that the belief in the one and only God does not mean that God is only one universally, but that understanding can only be owned by religious people and stored in belief. But in Pancasila, the nature of the one value is interpreted that it is noble for all Gods who are just, merciful and merciful who must be imbued with one spirit by all Indonesian people. In the thought of Mohammad Arkoun who rejects the teachings of Islam in a sloganistic-formalistic manner, the concept of God Almighty can be the key to bringing Islam as rahmatan lil'alamin. According to him, fighting for Islam is no longer relevant by using it as a formal basis in the state, but it will be much more important to fight for Islam substantially by presenting it in the entire process of state life. Moreover, philosophically, the context of the first precepts of Pancasila from an Islamic perspective makes that the values of civility, justice, unity, and prosperity as the essence of the next precepts must be achieved with the concept of "God Almighty''. That is, based on Soekarno's thoughts on the first principle of Pancasila, then contextualized to Islam in terms of its divinity, through the internalization of Mohammad Arkoun's method of thinking, resulted in the conclusion that the message of Islam is the key to justice and prosperity.